Analysis of the structure and efficiency of national health care systems - Shalko, Myroslava; Andriushchenko, Anhelina (International Journal of Public Health Science (IJPHS), 2024)
It was noted that the right to health care is a key topic of discussion around the world, and ensuring the realization of this right and the opportunity to access the necessary medical care is in the spotlight. The realization of the right to health care in each country directly depends on the national health policy. The analysis is focused on assessing the effectiveness of health care systems of states according to several models. The data for this study were obtained from the existing WHO database, which provides accumulated data for groups of countries. Thus, it was possible to compare different countries, whose state health statistics may have their own characteristics. For data processing, an input-oriented analysis model of a dynamic network data shell was used. The analysis combines the use of traditional and non-traditional methods for measuring health performance. The analysis shows that there are no pure health systems financing models, most states use mixed funding models. The only way to reduce dependence on direct payments is for the government to encourage the use of a prepayment and risk pooling approach.